1997
DOI: 10.1021/bi962342g
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Reaction Coordinate of Photosynthetic Water Oxidation by Kinetic Measurements of 355 nm Absorption Changes at Different Temperatures in Photosystem II Preparations Suspended in Either H2O or D2O

Abstract: Flash-induced absorption changes at 355 nm were measured at different temperatures within the range of 2 degrees C Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
97
2
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(124 citation statements)
references
References 51 publications
23
97
2
2
Order By: Relevance
“…Through x-ray measurements, similar half-times were reported and assigned to Mn redox reactions (11), except that a lag time of 200 s was detected before Mn reduction during the S 4 -to-S 0 transition. The 2 H 2 O isotope effects on the S state transitions have been reported in the range of 1.3-to 1.4-fold (38).…”
Section: Discussionmentioning
confidence: 99%
“…Through x-ray measurements, similar half-times were reported and assigned to Mn redox reactions (11), except that a lag time of 200 s was detected before Mn reduction during the S 4 -to-S 0 transition. The 2 H 2 O isotope effects on the S state transitions have been reported in the range of 1.3-to 1.4-fold (38).…”
Section: Discussionmentioning
confidence: 99%
“…The activation energy was very low, about 10 kJ mol -1 (37,38). Taking the gross kinetical ruler of Moser et al (82) at face value and using the observed rate of electron transfer between Y Z and P 680 + , about 5 × 10 7 s -1 in oxygen-evolving PSII (8,37,(83)(84)(85)(86), we calculated a reorganization energy of about 0.5 eV (123,124). An even higher reorganization energy, 0.7 eV, has been obtained, for instance, for the electron transfer (in ∼200 ps) from bacteriopheophytin to Q A in the bacterial reaction center (see ref 82 and references therein).…”
Section: Discussionmentioning
confidence: 99%
“…[67][68][69] The activation energy increases by a factor of about 3 for S 2 →S 3 compared to that for the S 1 →S 2 transition. The authors attribute this marked difference in activation energy to the involvement of a significant structural change in the S 2 →S 3 transition that is absent in the S 1 →S 2 transition.…”
Section: Implication To the Mechanism Of Water Oxidationmentioning
confidence: 99%